PENGARUH EKSPOR DAN PRODUKSI TERHADAP HARGA BATUBARA INDONESIA PADA TAHUN 2018-2020 - Daniel Situmeang; Arif Setiawan (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2022)
Coal is one of source of fossil fuels that can be utilized in several industries such as power plants, cement, metallurgy, and others. Coal is produced for sale both domestically to meet domestic demand and for sale abroad (export). The sale of coal is an interaction between demand and supply which will affect the price. The problem in this study is related to how much the impact of coal exports and production on the coal prices based on monthly data from 2018 to 2020. This study aims to estimate the magnitude of the influence of these two variables on coal prices. The method used in this research is a quantitative method with a multiple regression approach. The results of the regression analysis based on monthly data from 2018 to 2020 obtained explain that coal exports have a positive effect on coal prices by 0.100648%, which means that if there is an increase in coal exports it will affect price increases by 0.100648%. However, coal production has a negative effect on coal prices of 0.217319%, which means that if there is an increase in coal production it will affect a decrease in coal prices. The results of the statistical t-test explained that coal exports and production did not significantly affect coal prices. From these results it can be concluded that coal exports have a positive effect and coal production has a negative effect on coal prices, but not significantly.